2012
DOI: 10.1002/macp.201100653
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and Molecular Study of Poly{4‐[4‐(hexyloxy)phenyl]ethynylphenyl methacrylate} in Dilute Solutions and Conformational Peculiarities of Brush‐Like Macromolecules

Abstract: Brush-like poly{4-[4-(hexyloxy)phenyl]ethynylphenyl methacrylate}s are synthesized using RAFT polymerization, fractionated and studied by molecular hydrodynamic methods. The values of the velocity sedimentation coeffi cient, the frictional ratio, and the intrinsic viscosity are obtained in toluene. The conformational and structural parameters of the studied poly mer chains are estimated by the use of theories that describe the hydrodynamic behavior of the wormlike cylinders without intra-chain excluded volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…It has been reported that the extent of branching is higher 289 [186,187,229,577] 290 [175,203,305] 291 [211] 295 [308] 301 [165] 306 CSSQMA [389] 302 [164] 303 [209] 304 [305] 307 [578,579] 308 [579] 305 [212] 297 [188] 298 [201] 299 [201] 300 [387] 292 [189] 293 [173] 294 [210] Glycerol monomethacrylate Solketal methacrylate 296 [197,390] for conventional radical polymerization than for RDRP (ATRP, RAFT, and NMP). [443] A qualitative explanation was proposed in terms of the differences in the concentrations of short-chain radicals between RDRP and conventional radical polymerization.…”
Section: Acrylatesmentioning
confidence: 99%
“…It has been reported that the extent of branching is higher 289 [186,187,229,577] 290 [175,203,305] 291 [211] 295 [308] 301 [165] 306 CSSQMA [389] 302 [164] 303 [209] 304 [305] 307 [578,579] 308 [579] 305 [212] 297 [188] 298 [201] 299 [201] 300 [387] 292 [189] 293 [173] 294 [210] Glycerol monomethacrylate Solketal methacrylate 296 [197,390] for conventional radical polymerization than for RDRP (ATRP, RAFT, and NMP). [443] A qualitative explanation was proposed in terms of the differences in the concentrations of short-chain radicals between RDRP and conventional radical polymerization.…”
Section: Acrylatesmentioning
confidence: 99%
“…This is supposed to be a result of the dense comb-like structure of the polymers that hinders the formation of loose polymer coils (e.g., as in the case of PS) in solution. 14 In contrast to the homopolymers P1-P3 and P2-stat-P3, the PMMA-containing copolymer's molar masses were determined only by SEC ( Table 1). The accordance between the theoretical molar masses and the measured ones leads to the conclusion that SEC provides reliable values.…”
Section: Structural Characterization and Molar Massesmentioning
confidence: 99%
“…[11][12][13] The dense packing of the side chains covalently bound to a linear backbone causes confined and compact structures, in particular, worm-like conformations. 14 Hence, notable chain end effects can be observed. The incorporation/attachment of conjugated oligomers to nonconjugated backbones leads to a variety of different structures due to the wide range of possible pendant molecules revealing chemical stability, photoconductivity of the attached p-electron systems, and an invariance of the standard oxidation/reduction potential with the degree of substitution.…”
mentioning
confidence: 99%
“…7,8 In gra polymers, side chains offer the possibility of dense packing, resulting in compact and conned structures. 9 In order to combine the well-dened optoelectronic properties of monodisperse oligomer moieties and typical polymer properties, e.g., mechanical and chemical stability as well as processability into thin lms, conjugated side chains have been attached to aliphatic polymers. Several p-conjugated oligomers have been successfully implemented as side chains, for instance triphenylamines, [10][11][12][13] oligothiophenes, 14 carbazoles, 15 perylenes, 16 phenylene ethynylenes 17 and diphenyl acetylenes.…”
Section: Introductionmentioning
confidence: 99%